Nonreceptor protein tyrosine and lipid phosphatases in type I fc(epsilon) receptor-mediated activation of mast cells and basophils - Heneberg, Petr; Dráber, Petr (International archives of allergy and immunology, 2002)
Protein tyrosine and lipid phosphorylations are early and critical events in type 1 Fc(epsilon) receptor (Fc(epsilon)RI)-mediated activation of mast cells and basophils. Tyrosine phosphorylation of Fc(epsilon)RI subunits as well as other signal transduction molecules reflects the balance between the action of protein tyrosine kinases and phosphatases. Similarly, the phosphate content of inositol phospholipids, involved in the recruitment of signalling molecules to the plasma membrane and the generation of secondary messengers, is the net result of the opposing effects of phosphoinositide kinases and lipid phosphatases. This review summarizes the current understanding of the structural and functional aspects of nonreceptor protein tyrosine phosphatases (SHP-1, SHP-2, HePTP, PTP20, PRL1, PRL2, PTP-MEG1 and PTP-MEG2) and lipid phosphatases (SHIP and SHIP2) in the activation of mast cells and basophils after Fc(epsilon)RI aggregation. New approaches towards a deeper understanding of the role of phosphatases in mast cell physiology are also discussed.
Keywords: Basophils; Models, Immunological; receptory IgE; tyrosinfosfatasy; Mast Cells; modely imunologické; Protein Structure, Tertiary; terciární struktura proteinů; fosfatidylinositol-3,4,5-trisfosfát-5-fosfatasy; Receptors, IgE; signální transdukce; bazofily; fosfatasy; tyrosinfosfatasa nereceptorového typu 1; Phosphoric Monoester Hydrolases; Protein Tyrosine Phosphatase, Non-Receptor Type 1; Signal Transduction; lidé; Protein Tyrosine Phosphatases; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Humans; mastocyty